2019
DOI: 10.1002/aid2.13141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of discontinuation of aspirin on colonoscopic postpolypectomy bleeding

Abstract: Bleeding is one of the most common complications after colonoscopic polypectomy. Several factors associated with postpolypectomy bleeding (PPB) have been discussed, but whether aspirin increases the risk remains controversial, and the effect of the discontinuation of aspirin on PPB is still unclear. We aim to identify the risk factors of PPB and to assess the effect of aspirin on PPB. Patients undergoing colonoscopic polypectomy between November 2013 and September 2014 were recruited to the retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A retrospective study showed that discontinuation of aspirin was an independent protective factor for PPB (hazard ratio [HR], 0.13; 95% CI, 0.03–0.75; p =0.022), especially when the polyp was ≥12 mm. 52 …”
Section: Recommendations For the Management Of Antithrombotic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study showed that discontinuation of aspirin was an independent protective factor for PPB (hazard ratio [HR], 0.13; 95% CI, 0.03–0.75; p =0.022), especially when the polyp was ≥12 mm. 52 …”
Section: Recommendations For the Management Of Antithrombotic Agentsmentioning
confidence: 99%
“…the polyp was ≥12 mm. 52 A large retrospective cohort study including consecutive patients undergoing colonoscopic polypectomy reported that thromboembolic events occurred in two out of 487 patients (0.41%) who continued aspirin during the procedures and two out of 568 patients (0.35%) who stopped aspirin before the procedure. 53 Considering the rate of thromboembolic events in aspirin users, aspirin may be discontinued during ultra-highrisk procedures.…”
Section: Recommendations For the Management Of Antithrombotic Agentsmentioning
confidence: 99%
“…Yao et al investigated the risk factors of PPB and effect of aspirin on PPB. Previous studies usually divided PPB to immediate (intraprocedural bleeding) and delayed (postprocedural bleeding) despite various definitions among studies.…”
mentioning
confidence: 99%